Single fraction multimodal image guided focal salvage high-dose-rate brachytherapy for recurrent prostate cancer - Zamboglou, Constantinos; Rischke, Hans-Christian; Meyer, Philipp Tobias; Knobe, Sven; Volgeova-Neher, Natalja; Kollefrath, Michael; Jilg, Cordula Annette; Grosu, Anca Ligia; Baltas, Dimos; Kroenig, Malte (Journal of Contemporary Brachytherapy, 2016)
Purpose: We present a novel method for treatment of locally recurrent prostate cancer (PCa) following radiation therapy: focal, multimodal image guided high-dose-rate (HDR) brachytherapy. Material and methods: We treated two patients with recurrent PCa after primary (#1) or adjuvant (#2) external beam radiation therapy. Multiparametric magnetic resonance imaging (mpMRI), choline, positron emission tomography combined with computed tomography (PET/CT), or prostate-specific membrane antigen (PSMA)-PET combined with CT identified a single intraprostatic lesion. Positron emission tomography or magnetic resonance imaging – transrectal ultrasound (MRI-TRUS) fusion guided transperineal biopsy confirmed PCa within each target lesion. We defined a PET and mpMRI based gross tumor volume (GTV). A 5 mm isotropic margin was applied additionally to each lesion to generate a planning target volume (PTV), which accounts for technical fusion inaccuracies. A D90 of 18 Gy was intended in one fraction to each PTV using ultrasound guided HDR brachytherapy. Results : Six month follow-up showed adequate prostate specific antygen (PSA) decline in both patients (ΔPSA 83% in patient 1 and ΔPSA 59.3% in patient 2). Follow-up 3-tesla MRI revealed regressive disease in both patients and PSMA-PET/CT showed no evidence of active disease in patient #1. No acute or late toxicities occurred. Conclusions : Single fraction, focal, multimodal image guided salvage HDR brachytherapy for recurrent prostate cancer is a feasible therapy for selected patients with single lesions. This approach has to be evaluated in larger clinical trials.